Perancangan Model Dashboard E-Marketplace Bank Sampah Sebagai Sarana Informasi Berbasis Web - Marjuki, Arif; Cahyadi, Dede; Pramesti, Amanda Widya (Technomedia Journal, 2020)
In the current industrial era 4.0, technological advances are inevitable, with so many information and data needs that are very fast requiring innovation in displaying data that is processed into information that is accurate, fast, quantitative and relevant to support a decision obtained by the current user . Garbage banks are commonly used to sort and recycle to become a useful value. But in practice, the transaction process and data flow in waste bank management is constrained by the absence of recording and storage efficiently and effectively so that the loss of data is very risky for the seller. Therefore an information system is needed to be able to accommodate every sales and visitor update so that the seller does not need to record it manually. In making this dashboard use the Yii Framework tool because this viewboard uses the website as a media for its appearance. This research was made using the method of analysis, planning, design and prototype, the design of the e-marketplace dashboard is intended as a container of information from the data available for each sales transaction, so that it will display accurate and up-to-date information and facilitate monitoring.